Monitoring-data mechanism-driven dynamic evaluation method for slope safety. (August 2022) - Dong, Kai; Yang, Dewei; Chen, Jiankang; Zhou, Jingren; Li, Junru; Lu, Xiang; Pei, Liang; Kou, Qingjian
Abstract: Many high and steep slopes are formed in the construction of hydropower, highway, and railway projects. The long-term safety risk management and control problems are prominent. Slope deformation monitoring is one of the means to directly characterize the safety status of a slope, so it is of great significance to use slope deformation monitoring information to accomplish the dynamic evaluation of slope safety for safe engineering operations. In this study, the aging component of the slope displacement was separated using the empirical mode decomposition method. Combined with the response surface equation and the genetic optimization algorithm, a parameter back analysis method based on the aging displacement increment of the slope was proposed, and the determined calculation parameters can better reflect the creep characteristics of rock slope. Based on the results of the back analysis parameters, the most dangerous slip surface of the slope was determined using the strength reduction method, and the time series of the safety factor of the slope was obtained. Combining the dynamic coupling relationship between the slope displacement monitoring quantity and the slope stability, a surrogate model between the safety factor of the slope and the displacement aging component was constructed for the first time. A novel monitoring-data mechanism-driven dynamic evaluation method for slope safety was proposed considering the creep characteristics of the slope. The method was applied to an engineering slope example. The relative errors of the fitting and the prediction results of the dynamic evaluation model were less than 1%. The dynamic quantitative evaluation of the slope safety based on the displacement monitoring data was achieved. This provided an effective guarantee for slope safety control.